2007
DOI: 10.1134/s0006297907100069
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oxidative modification of low density lipoproteins under conditions of oxidative and carbonyl stress

Abstract: Low-molecular-weight aldehydes (glyoxal, methylglyoxal, 3-deoxyglucosone) generated on autooxidation of glucose under conditions of carbonyl stress react much more actively with amino groups of L-lysine and epsilon-amino groups of lysine residues of apoprotein B-100 in human blood plasma low density lipoproteins (LDL) than their structural analogs (malonic dialdehyde (MDA), 4-hydroxynonenal) resulting on free radical oxidation of lipids under conditions of oxidative stress. Glyoxal-modified LDL aggregate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 79 publications
2
41
0
3
Order By: Relevance
“…The content of MDA-modifi ed LDL was elevated by 33% in hypercholesterolemic patients, but remained practically unchanged in probands with hypertriglyceridemia (Table 1). These data are consistent with the results of our previous experiments demonstrating the important role of LDL peroxidation in the pathogenesis of atherosclerosis and confi rm the assumption that disturbances in lipid metabolism during atherogenesis can contribute to activation of free radical processes [1,2].Published data suggest the existence of interrelations between atherosclerosis and elevated content of MDA-modifi ed LDL in blood plasma [6,7,10,11]. Our study revealed a strong positive correlation between the concentration of total CH or LDL CH and content of oxidized (MDA-modifi ed) LDL in blood plasma from probands (r=0.68 and 0.72, respectively; p<0.05; Figs.…”
supporting
confidence: 92%
“…The content of MDA-modifi ed LDL was elevated by 33% in hypercholesterolemic patients, but remained practically unchanged in probands with hypertriglyceridemia (Table 1). These data are consistent with the results of our previous experiments demonstrating the important role of LDL peroxidation in the pathogenesis of atherosclerosis and confi rm the assumption that disturbances in lipid metabolism during atherogenesis can contribute to activation of free radical processes [1,2].Published data suggest the existence of interrelations between atherosclerosis and elevated content of MDA-modifi ed LDL in blood plasma [6,7,10,11]. Our study revealed a strong positive correlation between the concentration of total CH or LDL CH and content of oxidized (MDA-modifi ed) LDL in blood plasma from probands (r=0.68 and 0.72, respectively; p<0.05; Figs.…”
supporting
confidence: 92%
“…'Dicarbonyl-free radicals' are a normal byproduct of metabolism, the formation of which is accelerated in diabetes (28), and is involved in diabetic complications. Thus, the rationale for employing polyphenolics such as procyanidins and reactive carbonyl quenching amino acids, such as arginine and lysine (29,30), was not only to improve individual biochemical markers, but also to prevent damage by excess serum sugar, thereby negating sugar free radicals and sequestering oxidative radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely reactive carbonyl compound is HNE which possesses electrophilic double bond, carbonyl and hydroxyl groups. However, such dialdehydes as GO, MGO, and 3-DG are much more active than HNE and MDA (Lankin et al, 2007). In addition, acrolein reacts with thiols 100-fold more rapidly than HNE (Witz, G. 1989.…”
Section: Wwwintechopencommentioning
confidence: 99%